2018
DOI: 10.1177/0885328218763318
|View full text |Cite
|
Sign up to set email alerts
|

Released fibroblast growth factor18 from a collagen membrane induces osteoblastic activity involved with downregulation of miR-133a and miR-135a

Abstract: We have developed a unique delivery system of growth factors using collagen membranes (CMs) to induce bone regeneration. We hypothesized that fibroblast growth factor18 (FGF-18), a pleiotropic protein that stimulates proliferation in several tissues, can be a good candidate to use our delivery system for bone regeneration. Cell viability, cell proliferation, alkaline phosphatase activity, mineralization, and marker gene expression of osteoblastic differentiation were evaluated after mouse preosteoblasts were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…Another finding in our study was that up-regulated exosomal miR-133a decreased CVF, reduced the expression of collagen I and collagen III in rats with VMC. A article has elucidated that released fibroblast growth factor-18 from a collagen membrane causes osteoblastic activity participating in down-regulated miR-133a [ 31 ]. In vitro excessive expression of miR-133a depresses cardiomyocyte hypertrophy and reduces collagen expression [ 32 ], as evidenced in another study.…”
Section: Discussionmentioning
confidence: 99%
“…Another finding in our study was that up-regulated exosomal miR-133a decreased CVF, reduced the expression of collagen I and collagen III in rats with VMC. A article has elucidated that released fibroblast growth factor-18 from a collagen membrane causes osteoblastic activity participating in down-regulated miR-133a [ 31 ]. In vitro excessive expression of miR-133a depresses cardiomyocyte hypertrophy and reduces collagen expression [ 32 ], as evidenced in another study.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of drug delivery for bone regeneration, this type of kinetics is desirable because it promotes a prolonged duration for the development of new bone. In the CMs with GFs unit developed in our study, this release kinetics has been confirmed for up to 14~21 days [96][97][98][99][100][101]. The total cumulative amount of sustained release ranged from 30% to ≈100%.…”
Section: A Growth Factor Released From a CMsupporting
confidence: 70%
“…4.5. CMs with FGF-18 (CM/FGF-18) [99] We have created a novel delivery system based on proprietary growth factor with CMs to induce bone regeneration. We hypothesized that FGF-18, a multifaceted protein that elevates proliferation in multiple tissues, could be a good candidate for bone reconstruction using our delivery system.…”
Section: Cms With Op-1 (Cm/op-1) [98]mentioning
confidence: 99%
“…miR‐133a and miR‐135a are involved in the inhibition of osteogenic factors including runt‐related transcription factor 2 (Runx2) and Smad5. Recombinant FGF18, released from collagen membranes, promoted osteoblastic activity by decreasing the expression of miR‐133a and miR‐135a to allow increased expression of osteogenic factors (Imamura et al, 2018). Cyclic mechanical loading‐induced osteogenic differentiation of human periodontal ligament cells and decreased expression of endogenous miR‐195‐5p.…”
Section: Microrna Regulation Of Fgf Signalingmentioning
confidence: 99%